2020
DOI: 10.14710/ik.ijms.25.1.7-14
|View full text |Cite
|
Sign up to set email alerts
|

Oral Administration of Alginate Oligosaccharide from Padina sp. Enhances Tolerance of Oxygen Exposure Stress in Zebrafish (Danio rerio)

Abstract: Alginate is rich in bioactive compounds and has been known to act as a stimulator on the innate immune system. The objective of this study is to determine polysaccharide and oligosaccharide alginate yield, that percentage inhibition with a different type of extraction, to evaluate growth performance as well as immune response by oxygen stress tolerance. Thermal heating with oven laboratory at 140oC for 4.5 hr was done to breakdown the polysaccharide into oligosaccharide. The extraction was conducted by macerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…The treatment of unoxygen exposure in L. calcalifer exhibits that oral supplementation of alginate in feed resulted better survival rate compared to the control. Yudiati et al (2020) reported the similar result with low molecular weight sodium alginate in Zebrafish (Danio rerio), and Sudaryono et al (2018) with Sargassum sp. powder feed supplementation in Litopenaeus vannamei.…”
Section: Hematocrit and Hemoglobinsupporting
confidence: 54%
“…The treatment of unoxygen exposure in L. calcalifer exhibits that oral supplementation of alginate in feed resulted better survival rate compared to the control. Yudiati et al (2020) reported the similar result with low molecular weight sodium alginate in Zebrafish (Danio rerio), and Sudaryono et al (2018) with Sargassum sp. powder feed supplementation in Litopenaeus vannamei.…”
Section: Hematocrit and Hemoglobinsupporting
confidence: 54%
“…Research from Yudiati et al, (2016; and Lee at al., (2009) clearly described that alginate is an effective supplement to suppress replication of severe pathogenic bacteria and White Spot Syndrome Virus Disease by improving the shrimp immune system and transcription of immune gene expression. Alginate oligosaccharide which produces form thermal heating (Yudiati et al, 2018) also enhanced the tolerance of Zebrafish in oxygen exposure tests (Yudiati et al, 2020).…”
Section: Probioticmentioning
confidence: 97%
“…(Yudiati and Isnansetyo, 2017) and Padina sp. (Yudiati et al, 2020). Alginate has been shown to the increase non-specific immunity of shrimp (Yudiati et al, 2016;Yudiati et al, 2019) and is capable of improving the resistance to diseases such as V. parahaemolyticus infection (Cheng and Yu, 2013), V. harveyi (Jiang et al, 2017), V. alginolyticus (Cheng et al, 2004;Cheng et al, 2005;Cheng et al, 2007;Cheng et al, 2008), Streptococcus agalactiae (Van Doan et al, 2016), S. iniae (Harikrishnan et al, 2011), White Spot Syndrome Virus (WSSV) (Yudiati et al, 2019), Streptococcus sp.…”
Section: Introductionmentioning
confidence: 99%